Influence of biased feedback on performance in a Vernier discrimination task - Yang, Chenfan; Xu, Ziran; Zhong, Yaoyao; Wang, Tianze (Frontiers in Psychology, 2023)
The influence of feedback on performance is a topic of ongoing debate, with some previous studies finding it to be ineffective, while others have discovered that it can be helpful or harmful. One possible reason for these inconsistent results may be that feedback can create a conflict between a person's beliefs and the sensory information they receive. In the present study, we used a Vernier discrimination task to examine the influence of biased feedback on performance, as this type of feedback is most likely to create conflict. Biased feedback refers to feedback that does not align with the subjects' choices. The Vernier discrimination task is a type of psychophysical task that is often used to measure an individual's ability to perceive differences in the position or orientation of two visual stimuli. The task involves presenting two stimuli, one of which is slightly offset from the other, and asking the individual to determine the direction and magnitude of the offset. In Experiment 1, feedback was provided after each trial using large-offset verniers as guidance. The large-offset verniers always received correct feedback, but the small and medium-offset verniers might receive biased feedback. In Experiment 2, feedback was provided after each block of eight verniers. In Experiment 3, we removed the large offset vernier to investigate the influence of block feedback on the signal and noise. The results showed that the accuracy for the target vernier decreased due to biased feedback in both the trial feedback (Experiment 1) and the block feedback (Experiment 2). However, in Experiments 1 and 2, performance improved when feedback was absent. Moreover, if the difference between the two types of stimuli is great, the individual will engage in encoding learning rather than decision learning (Experiments 1 and 2). If the discrimination between the two types of stimuli is low, an individual's ability to discriminate noise is more vulnerable to the influence of biased feedback than the ability to discriminate the signal (Experiment 3). These results are discussed in relation to the mechanism of biased feedback, the process of encoding learning, the monitoring of internal feedback, and the generalization of false decisions.